PEMIKIRAN SASMITANING SUKMA TENTANG PEMBAHARUAN TASAWUF DAN IMPLIKASINYA TERHADAP GERAKAN DAKWAH DI KULONPROGO - Hasan, Moh. Abdul Kholiq; Abdurrohim, Abdurrohim (Universitas Muhammadiyah Surakarta, 2019)
Tasawuf (mysticism) is generally considered as deviation by most of Muslim community itself. One of religious figures who is active in preaching and interesting in Indonesia as well as having a big influence because of this thought is Ki H SS. Ki H SS is able to present the tasawuf teaching based on al Quran verses and Hadist. An interesting thing to be analyzed is